PENERAPAN MODEL GIVING QUESTION AND GETTING ANSWER (GQGA) UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Santi; Umiyati Jabri; Rosdiawati (STKIP Subang, 2026)
This study aims to improve Indonesian language learning outcomes through the implementation of the Giving Question and Getting Answer (GQGA) learning model in fourth-grade elementary school students. The research employed Classroom Action Research conducted in two cycles consisting of planning, action, observation, and reflection stages. The subjects were 16 students of grade IV at SDN 12 Enrekang. Data were collected through observation, tests, and documentation and analyzed using descriptive quantitative techniques by calculating mean scores and classical completeness. The findings indicate a significant improvement in learning outcomes, where the average score increased from 51.93 in the pre-cycle to 61.38 in cycle I and 82.81 in cycle II, while learning completeness improved from 0% to 37.5% and reached 81.25%. In addition, the implementation of the GQGA model enhanced student participation, confidence, and engagement during the learning process. Therefore, the GQGA model is considered effective in improving Indonesian language learning outcomes at the elementary school level.